2018
DOI: 10.1177/2192568218756877
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Spine Surgery Among Patients Who Have Had Prior Bariatric Surgery

Abstract: Study Design:Retrospective cohort study.Objectives:We hypothesized that spine surgery patients with a history of bariatric surgery do not differ in expectations of surgery, perceived benefit of surgical intervention, or physician determined outcome of surgery from patients with no history of bariatric surgery.Methods:Patients seen in our spine clinic between January 1, 2 009 and December 30, 2 010 were reviewed. Included patients had a history of bariatric surgery and were 18 to 89 years old. We compared their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Conversely, other studies have demonstrated no significant improvement associated with prior BS in elective TJA patients. 24,25 In the elective spine surgical literature, Jensen et al 26 conducted a single-institution study of 210 elective lumbar and cervical spine surgeries and found no significant difference in clinical outcomes between cervical spine surgery patients who received a prior BS versus those who did not. Given the small sample size, it is possible that the study may be underpowered to demonstrate a true effect that may be present.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, other studies have demonstrated no significant improvement associated with prior BS in elective TJA patients. 24,25 In the elective spine surgical literature, Jensen et al 26 conducted a single-institution study of 210 elective lumbar and cervical spine surgeries and found no significant difference in clinical outcomes between cervical spine surgery patients who received a prior BS versus those who did not. Given the small sample size, it is possible that the study may be underpowered to demonstrate a true effect that may be present.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated significantly worse preoperative and postoperative ODI and Neck Disability Index (NDI) scores in patients who had bariatric surgery before spine surgery. 25 These patients also exhibited worse postoperative pain as measured by the visual analog scale (VAS). Bariatric surgery is also associated with metabolic disorder and nutritional deficiencies due to altered digestion that could compromise surgical success.…”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…Functional outcomes in patients undergoing bariatric surgery before spine surgery have also shown mixed results. One study demonstrated significantly worse preoperative and postoperative ODI and Neck Disability Index (NDI) scores in patients who had bariatric surgery before spine surgery 25. These patients also exhibited worse postoperative pain as measured by the visual analog scale (VAS).…”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…In addition to the myriad medical comorbidities associated with obesity, such as diabetes, coronary heart disease, and pulmonary disease, obesity in of itself has been shown to be an independent risk factor for complications associated with spine surgery. 9 -12 For example, in the Spine Patient Outcomes Research Trial (SPORT), 9 the 4-year follow-up data demonstrated a high complication profile for obese patients (infection and revision rates, as compared to nonobese patients) though similar improvements in patient-reported outcomes in the surgical group were reported. McGuire et al 12 in a subgroup analysis of the 4-year SPORT data for obese patients, particularly those with BMI >35 kg/m 2 (Class II and Class III obesity), reported worse outcomes in complications, operative time, and baseline patient-reported outcomes particularly in the degenerative spondylolisthesis group.…”
Section: Obesitymentioning
confidence: 99%
“…There are a few studies that have examined the role of surgical weight loss and its effect on minimizing complications in patients undergoing spine surgery. 10,14,17 However, a recent retrospective cohort study by Jensen et al, 10 which looked at reported outcomes of cervical and lumbar surgery, demonstrated that patients who had undergone bariatric surgery had worse reported outcomes and satisfaction following lumbar surgery than their counterparts. We have a paucity of data to guide us regarding nonsurgical or surgical weight loss, and further studies are necessary to suggest one intervention over the other.…”
Section: Obesitymentioning
confidence: 99%